Abnormal adsorption and desorption behavior of pharmaceutical drugs on polystyrene microspheres. Issue 32 (3rd April 2017) - Wang, Teng; Zheng, Yajun; Wang, Xiaoting; Wang, Qiang; Ke, Congyu; Austin, Daniel E.; Han, Xiaoxiao; Zhang, Zhiping
Abstract : We report an abnormal adsorption and desorption behavior where a stronger adsorption interaction between polystyrene particles and pharmaceutical drugs results in preferable desorption behavior. Abstract : Herein we report an abnormal adsorption and desorption behavior where a stronger adsorption interaction between polystyrene particles and pharmaceutical drugs results in preferable desorption behavior. This behavior is contrary to the conventional view, in which a weaker adsorption interaction would lead to a more favorable desorption behavior of target molecules at solid surfaces. Different from other materials, numerous experimental results from a combination of mass spectrometry and infrared spectroscopy indicated quantitatively that the adsorption and desorption behavior of pharmaceutical drugs on polystyrene were independent of drug structure and solvent, while the intermolecular hydrogen bond interaction between polystyrene and the drug played a critical role in determining the adsorption and desorption behavior.